European rescue and recovery programmes against the Corona crisis - Hubertus Bardt; Sandra Parthie; Ciro Rapacciuolo; Livio Romano; Christian Helmenstein; Jyrki Ali-Yrkkö; Emmanuel Jessua (Institut der deutschen Wirtschaft (IW), 2020)
The current crisis is different from the situation 2008/2009, but again it is a tremendous challenge for the economies across Europe. The Corona-crisis is hitting the economies symmetrically, though with differences in magnitude levels, while the 2009 crisis was primarily a crisis of the banking industry and the manufacturing sector. This time, value chains are substantially affected. As the virus does not hit all countries at the same time, there will be distortions in the value chains over the next months. The assessments on the impact on national GDPs range from a best-case scenario -5% for Germany to a worst-case scenario of -12% for Italy. To deal with the impact of the crisis a European rescue programme is needed immediately, including bringing down infection rates and providing sufficient medical equipment and services. Regarding the economic support, the comprehensive efforts by the ECB and the Commission, including loosening the rules concerning state aid and the provision in the context of the SURE programme for short time work are very welcome. In a second phase, Europe will need a common recovery programme fostering economic development and coming back to sustainable growth quickly. Europe must secure open borders for goods, services and labour, which are crucial for the maintenance of the single market and for restarting cross-European value chains. Europe needs a large-scale and timely initiative to foster growth through public and private investments, focusing on health, technology, and the green economy. The Green Deal should play a key role for the design of the economic recovery programme. The 1.5 trillion euro plan foreseen by the Commission is appropriate to address the challenge faced by European economies. However, to avoid asymmetric rebounds within the EU after the emergency, the European recovery plan must be implemented soon and in a coordinated fashion. Unilateral national actions such as intra-EU border closures should be avoided as they increase uncertainty, lower business confidence, and raise costs. As supply chains are closely knit between EU member states, a common strategy for exiting the crisis will be of paramount importance to re-establish normal economic relationships among European firms and maintain the international competitiveness of the European industry.
Keywords: F02; H12; I15; 330